1989
DOI: 10.1002/ijc.2910430205
|View full text |Cite
|
Sign up to set email alerts
|

Structure and expression of c‐erbB‐2 and EGF receptor genes in inflammatory and non‐inflammatory breast cancer: Prognostic significance

Abstract: C-erbB-2 and epidermal growth factor receptor (EGFR) genes were independently shown to be associated with breast cancer progression. In this report, we have analyzed the structure and expression of these 2 genes in the same tumor specimens of a large series of breast cancers. Two clinical types of tumor were studied: inflammatory (IBC) and non-inflammatory breast cancers (NBC) obtained from 221 untreated patients at different clinical stages. Amplification and over-expression of the c-erbB-2 proto-oncogene wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
101
1
2

Year Published

1991
1991
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(113 citation statements)
references
References 34 publications
9
101
1
2
Order By: Relevance
“…26 As such, there are currently several prospective studies evaluating inhibitors of angiogenesis (eg, bevacizumab) for the treatment of IBC. 27 A higher frequency of overexpression of human epidermal growth factor receptor 2 (HER2) among IBC tumors compared with non-IBC tumors has also been reported, 28,29 making HER2-directed targeted therapy with adjuvant trastuzumab important. Women In conclusion, in this large population-based study, we demonstrated that in the era of the use of anthracyclines and taxanes, survival differences between women with stage IIIB/C IBC and those with non-IBC LABC are still present, with differences observed early.…”
Section: Discussionmentioning
confidence: 99%
“…26 As such, there are currently several prospective studies evaluating inhibitors of angiogenesis (eg, bevacizumab) for the treatment of IBC. 27 A higher frequency of overexpression of human epidermal growth factor receptor 2 (HER2) among IBC tumors compared with non-IBC tumors has also been reported, 28,29 making HER2-directed targeted therapy with adjuvant trastuzumab important. Women In conclusion, in this large population-based study, we demonstrated that in the era of the use of anthracyclines and taxanes, survival differences between women with stage IIIB/C IBC and those with non-IBC LABC are still present, with differences observed early.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies have varied considerably but several studies have found consistent results with respect to certain prognostic factors. The original study reported by Slamon et al (1987) showed a positive association between c-erbB-2 expression and the number of involved axillary nodes, this finding has not been generally reproducible but finds some support in three other studies (Tandon et al, 1989;Guerin et al, 1989;May et al, 1990) and indirectly in the study by Zhou et al (1989) ship between c-erbB-2 expression and other markers of differentiation. Ploidy has previously been investigated by two groups neither of whom found any significant association (Tavassoli et al, 1989;Ro et al, 1989) At least 20 other groups have now published data concerning the prognostic significance of c-erbB-2, of these only four groups have failed to find a prognostic effect of c-erbB-2 in at least one sub group (Zhou et al, 1989;Ali et al, 1988;Gusterson et al, 1988;Barnes et al, 1988).…”
mentioning
confidence: 88%
“…The overexpression of the receptor protein confers a transformed phenotype to NIH 3T3 cells 1 and could be demonstrated in various human malignancies. Different authors reported egfr amplifications in 0-15% of human breast carcinomas 2,3 and EGFR protein overexpression in 16.4%. 4 Although, numerous studies have shown its prognostic significance, [4][5][6][7] the most recent literature characterized EGFR as a factor of doubtful prognostic significance in human breast cancer.…”
mentioning
confidence: 99%